Applied Ethics in Mental Health Care : An Interdisciplinary Reader - Paul S. Appelbaum (The MIT Press, 2013)
For mental health professionals, there is no scarcity of ethical challenges. Some of the conundra that arise in everyday mental health work derive from the nature of the disorders and conditions that mental health professionals evaluate and treat. A second set of ethical issues originates in the treatments we use. Additional layers of moral complexity are contributed by the settings in which mental health professionals work. Taken together, it can safely be said that ethical challenges inhere in every aspect of mental health practice.